MITIGATION STRATEGIES IN INDONESIAN HOSPITALS FOR INFECTIOUS DISEASE PREVENTION - Indra Sari; Pudji Lestari (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Background: Indoor air pollution poses significant health risks. Prolonged exposure in contaminated environments heightens disease transmission risks. The COVID-19 pandemic has underscored the urgency for effective ventilation and air quality management in hospitals. Purpose: This study investigates the relationship between environmental factors (temperature, humidity, lighting, occupancy density, and airborne germ counts) and airborne microbiology control in hospital rooms. It aims to establish a secure air management system to reduce infectious disease transmission and provide references for hospital mitigation strategies. Review: This article method uses the systemic review. Information is taken from e-book sources, websites, and search engines. After filtering and adjusting the research variables, 12 articles were analyzed, consisting of 6 from google scholar articles and 6 articles from the Science Direct database. A systematic review examined (1) Airborne Transmission and Mitigation Strategies, (2) Infection Control in Healthcare Settings, (3) Infectious Disease Prevention and Early Detection, and (4) Specific Contexts and Impact of Infectious Diseases. It highlights the importance of ventilation, temperature control, humidity regulation, air cleanliness, and air pressure settings in minimizing infection risks. Result: The review indicates that effective ventilation, appropriate temperature, humidity, and air cleanliness (filtration) are essential for maintaining indoor air quality and reducing infection risks. Conclusion: Environmental factors are critical in controlling infectious disease transmission in hospitals. Effective air management systems are vital for the health and safety of patients, healthcare workers, and visitors. This study provides valuable insights into hospital mitigation strategies and emphasizes the need for continuous attention to air quality standards to prevent future outbreaks.